Research of the state of internal surfaces of a supercritical water loop after a session of irradiation - Azarov, A.I.; Bakai, A.S.; Boriskin, V.N.; Bocharov, V.A.; Gorenko, Yu.V.; Dolzhek, M.A.; Zaitsev, E.I.; Momot, V.A.; Solodovnikov, V.I.; Tytov, V.Yu.; Shelepko, S.V. (Вопросы атомной науки и техники, 2020)
Made of austenitic steel at the NSC KIPT, the supercritical water convection loop Loop-1a was running for more than 500 hours in the first experimental session (in 2011). The materials tested in the loop were placed into a stream of water (more than 50 g/s) at a temperature of 350…400°C, a pressure of 23… 25 MPa, and were irradiated by an electron beam with an energy of 10 MeV. Sediments that emerged on the inner surface of the loop were examined. The sediment mainly consisted of compounds of calcium and iron mixed with other elements. There is a possibility to increase corrosion induced by radiation due to dislocation damage, hydrogenation of metal and under the impact of active oxygen. Виготовлена з аустенітної стали в ННЦ ХФТІ надкритична водяна конвекційна петля Loop-1a в першому експериментальному сеансі (2011 рік) пропрацювала понад 500 год. Випробовувані у петлі матеріали перебували в потоці води (понад 50 г/с) при температурі 350…400°C, тиску 23…25 МПа і опромінювалися електронним пучком енергією 10 МеВ. Досліджували відкладення на внутрішній поверхні петлі, які складаються в основному із сполук кальцію і заліза з домішкою інших елементів. Можливе посилення корозії під дією випромінювання за рахунок дислокаційних ушкоджень, насичення воднем і активного кисню. Изготовленная из аустенитной стали в ННЦ ХФТИ сверхкритическая водяная конвекционная петля Loop-1a в первом экспериментальном сеансе (2011 год) проработала более 500 ч. Испытываемые в петле материалы находились в потоке воды (более 50 г/с) при температуре 350…400°C, давлении 23… 25 МПа и облучались электронным пучком энергией 10 МэВ. Исследовали отложения на внутренней поверхности петли, которые состоят в основном из соединений кальция и железа с примесью других элементов. Возможно усиление коррозии под действием излучения за счет дислокационных повреждений, наводорoживания и активного кислорода.